Biogasoline Production from Shallot Skin Waste with KOH-Clay Catalyst to Create Clean Energy - Keryanti Keryanti; Dhea Nurul Amalia; Anindya Indrita Putri; Della Agustia Marhani; Putri Vina Amalia; Anwar Muhamad Rizki (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Finding alternative fuels to replace fossil fuels has been made easier by the rise in the consumption of fuels like petrol and the fall in the production of national petroleum exploration activities. This research has been prompted using biomass as an alternative fuel. The primary raw material is shallot skin waste because it has enough lignocellulosic content to be used, one of which is to manufacture biogasoline by using the characteristics of petrol E10. A KOH-Clay catalyst is employed in a thermal and catalytic reaction to influence the reaction's pace. Starting with raw material preparation, conversion procedure, purification, and investigation of the physical properties of biogasoline at specific temperature fluctuations for an hour, the KOH-Clay catalyst is pretreated and characterised. It was discovered through this research that the montmorillonite KOH-Clay content was 5.73, indicating that the catalyst is hygroscopic and absorbs non-polar molecules, making it suitable for use as a catalyst with a pH of 6. As a result, at 60Â°C temperature circumstances, the best%yield results were attained of 35.025%. While the density value (0.950 gr/cm3) and colour (specific gravity, brownish yellow, and clear/bright) of the experimental results do not meet predetermined standards, they do when viewed from the viewpoint of physical parameters such as specific gravity (0.8358), oAPI biogasoline (37.794), and calorific value (18807.65 Btu/Ib). However, leftover shallot peels generally have the potential to be utilised as clean renewable energy.